(untitled) (El-Wahat Journal for Research and Studies, 2021)
ملخص تهدف هذه الدراسة إلى معرفة درجة استخدام نظام التكاليف على أساس الأنشطة (ABC) في المؤسسات الصغيرة والمتوسطة بولاية سكيكدة. شملت الدراسة مجموعة من المؤسسات بلغ عددها 24 مؤسسة تنشط بقطاعات مختلفة. توصلت الدراسة إلى أنه يوجد وعي وإدراك بأهمية استخدام نظام التكاليف على أساس (ABC) في المؤسسات الصغيرة والمتوسطة. غير أن نسبة تطبيقه جاءت ضعيفة بمؤسسة واحدة فقط. الكلمات الدالة: نظام التكاليف على أساس (ABC)، المؤسسات الصغيرة والمتوسطة، التكاليف التقليدية. Abstract: This study aims to know the degree of use of the Activity-Based Costing (ABC) in Small and Medium Enterprises in Skikda state. The study included a group of 24 institutions operating in different sectors. A study concluded that there is awareness of the importance of implementing Activity-Based Costing in Small and Medium Enterprises. However, its use rate was weak in only one institution. Key words: Activity-Based Costing in Small and Medium Enterprises, Traditional Costing.